Analisis Efektivitas Gas Turbine Generator dengan Metode Overall Equipment Effectiveness - Sayuti, M.; Maulinda, Silvira (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2019)
Increasing effectiveness is very important for companies to obtain success in their business processes. One example of increasing effectiveness is by evaluating the performance of production facilities in the company. PT. X is one of the chemical industry companies whose main production is urea fertilizer. One of the supporting processes of the production process is the Gas Turbine Generator (GTG) in the utility unit. In supporting the production process, GTG often experiences problems that directly hinder the production process. This study aims to analyze the effectiveness of Gas Turbine Generators by using the Overall Equipment Effectiveness (OEE) method. The results of the analysis show that the Turbine Gas Generator effectiveness level is 68.39% which indicates that the value of production effectiveness is considered reasonable, but shows there is a large space for improvement.